Students’ Perception of Using English Learning Youtube Channels in Improving Their Vocabulary - Nurhayati, Nurhayati; Nakluy, Erni Wendelina (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The main objective of this study is to understand students' perceptions of using English learning YouTube channels to improve vocabulary, viewed from the ease of use of English learning YouTube channels. This study uses a quantitative method with a descriptive analysis design. The instrument used in this study is a questionnaire. The respondents of this study are 8th-grade students at a public junior high school in Airmadidi, North Minahasa, with a total of 130 students. The analysis results show that students' perceptions of the ease of use of the English learning YouTube channel are positive, which can motivate them to improve their vocabulary. Students' perceptions of the usefulness of the English learning YouTube channel are also positive, meaning that the channel can help them in enhancing their vocabulary. Students' perceptions of attitudes towards using the English learning YouTube channel are also positive in improving their vocabulary. Therefore, it can be concluded that students' perceptions of using the English learning YouTube channel are positive, as reflected in the indicators of using the YouTube channel. Consequently, students can use the YouTube channel as an additional means to improve their vocabulary.